Role of Jalukaavcharana in Mukh Dushika (Acne Vulgaris) - Sharma, Girdhar Gopal; Khandelwa, Jyoti (International Research Journal of Ayurveda & Yoga, 2022)
More than 90% of the world’s population has experienced acne at some point in their lives, making it a fairly prevalent medical disease. Acne vulgaris is the most prevalent type of acne, accounting for 99 percent of all instances. Mukhdushika, which is produced by vitiated Kapha, Vata, and Rakta, is described in Ayurvedic scriptures in a way that is similar to acne vulgaris in modern medicine. Ayurvedic texts mention raktmokshana (bloodletting) as the primary method of treatment for raktaja and dermatological conditions. Jalaukawacharana is the preferred method of bloodletting in Sukumara, according to Acharya Susruta (tender nature person). As a bio-purifying technique, jalaukawacharana eliminates deeply ingrained pollutants by releasing blood, removing Srotasa, and calming vitiated Doha. Jalaukawacharana is highly effective in terms of its purifying and therapeutic effects. Important components of leech secretions include Destabilase, Bdellin, Histamine, Hyaluronidase, Fibrinases, and Collagenase, which have been shown to normalize and improve capillary as well as collateral blood circulation, express an anti-inflammatory effect, produce analgesia and anesthesia through saliva, and have an immunostimulant and immuno-modulating effect. An effort has been undertaken in this review to examine the potentials of leech therapy in treating Mukhdushika w.s.r to acne vulgaris.